Survival analysis and factors influencing survival time of adult HIV/AIDS patients receiving antiretroviral therapy from 2012 to 2022 in Chongqing, China: a retrospective cohort study - Huang, Yao; He, Ming; Zhang, Jinhua; Mu, Lihong; Tang, Cheng (Frontiers in Public Health, 2025)
BackgroundDespite expanded antiretroviral therapy (ART) coverage in China, AIDS remains a major public health challenge. This study aimed to assess survival outcomes and identify factors influencing survival time among HIV/AIDS patients receiving ART.MethodsThis study was a retrospective cohort study utilizing data on HIV patients receiving antiretroviral therapy in Jiulongpo District, Chongqing, from 2012 to 2022. Life tables estimated cumulative survival, Kaplan-Meyer compared survival between groups, and accelerated time to failure (AFT) modeling was used for analysis of factors influencing survival time.ResultsThe 1-, 3-, 5-, and 10-year cumulative survival rates were 94% (95% CI: 0.93 to 0.95), 90% (95% CI: 0.89 to 0.91), 86% (95% CI: 0.85 to 0.87), and 79% (95% CI: 0.76 to 0.81), respectively. Compared to patients aged 15–29, those aged 30–49 (TR = 0.22, 95% CI: 0.11 to 0.46, p < 0.01) and ≥50 (TR = 0.07, 95% CI: 0.03 to 0.15, p < 0.01) had shorter survival. Males (TR = 0.26, 95% CI: 0.17 to 0.38, p < 0.01), single (TR = 0.52, 95% CI: 0.33 to 0.84, p = 0.007), and divorced/widowed patients (TR = 0.67, 95% CI: 0.48 to 0.93, p = 0.018) had shorter survival compared to their counterparts. Infection via homosexual contact (TR = 0.21, 95% CI: 0.12 to 0.37, p < 0.01), injection drug use/other routes (TR = 0.09, 95% CI: 0.04 to 0.20, p < 0.01) was associated with shorter survival than heterosexual contact. Patients with tertiary (TR = 5.88, 95% CI: 3.05 to 11.33, p < 0.01), high school (TR = 2.86, 95% CI: 1.87 to 4.36, p < 0.01), and middle school education (TR = 1.93, 95% CI: 1.40 to 2.67, p = 0.002) had longer survival than those with primary/illiterate education. Baseline CD4 counts of ≥350 (TR = 3.26, 95% CI: 2.33 to 4.55, p < 0.01) and 200–349 cells/μL (TR = 2.73, 95% CI: 1.90 to 3.92, p < 0.01) were linked to longer survival compared to 0–199 cells/μL.ConclusionOlder age, males, lower educational attainment, homosexual contact, injection of drugs, and lower baseline CD4 levels are influential factors for shorter survival time in HIV/AIDS patients receiving ART. These findings may help inform clinical decision-making and targeted interventions to improve the long-term outcomes of people living with HIV.